2018
DOI: 10.1371/journal.pone.0192480
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin D deficiency causes inward hypertrophic remodeling and alters vascular reactivity of rat cerebral arterioles

Abstract: Background and purposeVitamin D deficiency (VDD) is a global health problem, which can lead to several pathophysiological consequences including cardiovascular diseases. Its impact on the cerebrovascular system is not well understood. The goal of the present work was to examine the effects of VDD on the morphological, biomechanical and functional properties of cerebral arterioles.MethodsFour-week-old male Wistar rats (n = 11 per group) were either fed with vitamin D deficient diet or received conventional rat … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
37
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 20 publications
(38 citation statements)
references
References 64 publications
1
37
0
Order By: Relevance
“…Lowered wall stress and reduced elastic modulus of arteriole segments were shown in the coronary artery from vitamin-D-deficient female rats [ 23 ]. Cerebral artery from vitamin-D-deficient male rats had attenuated wall stress [ 19 ]. Decreasing tendency of spontaneous tone of vitamin-D-deficient group was not significant, but moving in this direction may develop into a pre-hypertensive lesion due to long-term vitamin-D-deficient state.…”
Section: Discussion Limitations and Strengthsmentioning
confidence: 99%
See 3 more Smart Citations
“…Lowered wall stress and reduced elastic modulus of arteriole segments were shown in the coronary artery from vitamin-D-deficient female rats [ 23 ]. Cerebral artery from vitamin-D-deficient male rats had attenuated wall stress [ 19 ]. Decreasing tendency of spontaneous tone of vitamin-D-deficient group was not significant, but moving in this direction may develop into a pre-hypertensive lesion due to long-term vitamin-D-deficient state.…”
Section: Discussion Limitations and Strengthsmentioning
confidence: 99%
“…On the other hand, in case of vitamin-D-dependency, the organ or tissue cannot adapt by receptor-upregulation to the concentration changes, so it will be sensitive and vulnerable to vitamin D deficiency. According to our previous results from animal experiments, small vessels from the heart and brain are vitamin-D-dependent tissues, because in extreme vitamin-D-deficient milieu, they go through major changes [ 18 , 19 , 23 , 37 , 42 ], but these alterations are depending on which region the vessels are originated from. Both vitamin D deficiency and toxicity can induce smaller carotid artery diameter and larger wall thickness in male Wistar rat models within 4 weeks [ 43 ].…”
Section: Discussion Limitations and Strengthsmentioning
confidence: 99%
See 2 more Smart Citations
“…Furthermore, several studies have demonstrated the role of vitamin D3 in improving fertility disorders including polycystic ovarian syndrome, endometriosis, premature ovarian failure, male infertility, and in vitro fertilization techniques (Bakhshalizadeh et al, 2017; Pál et al, 2018). Vitamin D3 can, likewise, stimulate follicular development and improve the symptoms of PCOS (Çelik et al, 2018; Fang et al, 2017; Hadjadj et al, 2018).…”
Section: Discussionmentioning
confidence: 99%